Effective synthesis of Mg2CoH5 by reactive mechanical milling and its hydrogen sorption behavior after cycling - Verón, María Gisela; Condo, Adriana Maria; Gennari, Fabiana Cristina (Elsevier, 2013)
Fil: Verón, María Gisela. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comision Nacional de Energia Atomica. Centro Atomico Bariloche; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Area de Energía Nuclear. Instituto Balseiro; Argentina. Universidad Nacional de Cuyo; Argentina